Prof. Dr. Kostadin Pushara, academician, prof. dr Jasmin Jaganjac, prof. Dr. Zeljko Kovacevic, "Lobbying in modern conditions", Association of interest lobbying and promotion of the lobbying profession of Bosnia and Herzegovina, Sarajevo, 2017. - Jelenković, Predrag (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Na osnovu prethodnih brojeva Zbornika Pravnog fakulteta Univerziteta u Nišu, za Prikaz knjige nije predviđen sažetak